A practical framework for developing a virtual reality-based anatomy education application: key content and technical requirements - Erfan Esmaeeli; Amir Soleimani; Mohadeseh Sadat Khorashadizadeh; Leila Shahmoradi; Saeid Nekoonam; Sorayya Rezayi (Scientific Reports)
Abstract Anatomy is a requirement for medical education, which is necessary for the healthcare system to train professionals, improve their abilities, competencies, and practical experience, and fulfill society. The aim of this study is to provide a practical framework for developing virtual reality-based (VR) anatomy education applications by ascertain the technological and content specifications. This descriptive-analytical study was conducted in 2023–2024 and consisted of three steps. In the first step, related studies were reviewed to extract technical requirements, including software features and facilities. In the second step, VR software stores, such as Steam, Meta, and SideQuest were also examined to consider the most complete technical facilities, and similar software was considered. To this end, information related to the software, including the name of the software, headset and equipment, number of users (single user/multiple users), development tools, 3D material, anatomical position, and the key features are collected in Excel (version 2019). In the third step, seven curriculums of the anatomy course of the undergraduate degree in paramedical fields (including medical laboratory sciences, surgical technology, radiation therapy, radiology, health information technology, emergency care, and anesthesiology) were collected to identify the content requirements. Finally, a list of content and technical features was compiled. By examining software and literature, the research team for this study was able to determine the technological and content requirements. Following the elimination of duplicates, we were left with 80 technical and content requirements, divided into eight and two axes, respectively. The survey was distributed to 124 experts to assess technical and content requirements, and responses were received from a select group of participants, 35 experts. Consequently, we were able to identify 23 content needs that were divided into two axes and 57 technological requirements that were divided into eight categories. Statistical analysis was performed using SPSS (version 27). Developers may create educational anatomy software based on VR that not only engages learners but also significantly enhances their grasp of complex anatomical structures by carefully identifying and resolving technical and content needs.